Untargeted metabolomics unveiled the role of butanoate metabolism in the development of Pseudomonas aeruginosa hypoxic biofilm - Abdelhamid, Ahmed G.; Yousef, Ahmed E. (Frontiers in Cellular and Infection Microbiology, 2024)
Pseudomonas aeruginosa is a versatile opportunistic pathogen which causes a variety of acute and chronic human infections, some of which are associated with the biofilm phenotype of the pathogen. We hypothesize that defining the intracellular metabolome of biofilm cells, compared to that of planktonic cells, will elucidate the metabolic pathways and biomarkers indicative of biofilm inception. Disc-shaped stainless-steel coupons (12.7 mm diameter) were employed as a surface for static biofilm establishment. Each disc was immersed in a well, of a 24-well microtiter plate, containing a 1-mL Lysogeny broth (LB) suspension of P. aeruginosa ATCC 9027, a strain known for its biofilm prolificacy. This setup underwent oxygen-depleted incubation at 37°C for 24 hours to yield hypoxic biofilms and the co-existing static planktonic cells. In parallel, another planktonic phenotype of ATCC 9027 was produced in LB under shaking (200 rpm) incubation at 37°C for 24 hours. Planktonic and biofilm cells were harvested, and the intracellular metabolites were subjected to global untargeted metabolomic analysis using LC-MS technology, where small metabolites (below 1.5 kDa) were selected. Data analysis showed the presence of 324 metabolites that differed (p < 0.05) in abundance between planktonic and biofilm cells, whereas 70 metabolites did not vary between these phenotypes (p > 0.05). Correlation, principal components, and partial least square discriminant analyses proved that the biofilm metabolome is distinctly clustered away from that of the two planktonic phenotypes. Based on the functional enrichment analysis, arginine and proline metabolism were enriched in planktonic cells, but butanoate metabolism was enriched in biofilm cells. Key differential metabolites within the butanoate pathway included acetoacetate, 2,3-butandiol, diacetyl, and acetoin, which were highly upregulated in the biofilm compared to the planktonic cells. Exogenous supplementation of acetoin (2 mM), a critical metabolite in butanoate metabolism, augmented biofilm mass, increased the structural integrity and thickness of the biofilm, and maintained the intracellular redox potential by balancing NADH/NAD+ ratio. In conclusion, P. aeruginosa hypoxic biofilm has a specialized metabolic landscape, and butanoate pathway is a metabolic preference and possibly required for promoting planktonic cells to the biofilm state. The butanoate pathway metabolites, particularly acetoin, could serve as markers for biofilm development.